Faktor-Faktor yang Mempengaruhi Cakupan Skrining Kanker Serviks dan Loss to Follow Up pada Wanita dengan IVA Positif yang Menjalani Krioterapi di Negara Berkembang: Scoping Review - Adistyatama, Rizkha; Ganap, Eugenius Phyowai; Trirahmanto, Addin (JURNAL KESEHATAN REPRODUKSI, 2023)
Background: Cervical cancer is one of the main health problems in developing country and the second most common cancer in Indonesian women. For a better outcome, it is necessary to pay attention for discovery of the disease at an early stage. Single visit approach with visual inspection of acetic acid (VIA) followed by cryotherapy considered efficient and cost effective. However, low uptake of screening and loss to follow up after cryotherapy remain the biggest challenge.Objective: We aimed to identify factors affecting low uptake of cervical cancer screening and loss to follow up women with VIA positive undergone cryotherapy in developing countries.Method: This study is a literature review with scoping review design. Systematic search were conducted from databases PubMed, ScienceDirect, SAGE journals, Scopus and Google Scholar. Total 42 articles were selected for analysis, 35 articles discussed factors affecting cervical cancer screening uptake in developing countries and 7 articles discussed loss to follow-up women with VIA positive undergone cryotherapy.Results and Discussion: Factors identified affecting cervical cancer screening uptake and loss to follow up from demand side included lack of knowledge, perception and awareness, access constrain, fear or shame feeling and cost related problem. From supply side or healthcare system, these factors included lack of trained providers, lack of infrastructure, lack of information, coordination and communication, as well as ineffective administrative processes.Conclusion: Problems of cervical cancer screening uptake and loss to follow up after cryotherapy were identified from demand side and health service provider side. Recommendation of service improvement must consider influencing factors and limitations encountered on the field. Keywords: cervical cancer, screening, visual inspection of acetic acid, loss to follow-up, cryotherapy